ANALISIS PROGRAM PEDULI ANTI BULLYING UNTUK MENCEGAH MASALAH BELAJAR SISWA DI SMAN 3 TANA TORAJA - Siska Siska; Witarsa Tambunan (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2022)
Child abuse is not only done by the parents as the closest person but also done by the whole neighborhood, such as at school or in the society, so that the collaboration is needed that will give a good empact for the process of growth, teaching learning prosess, and in child social life. On the other hand, the school can also do an anti-abuse care programme to the whole stakeholder at school to prevent verbal and our verbal bullying at school so the teaching prosess can work out the way it was supposed to. This nesearch used literatune shidy by analyzing from varios research sources, e.book article, and interview results